Pengaruh Sumber Daya Pekerjaan Dengan Keterikatan Kerja Sebagai Mediasi Terhadap Perilaku Proaktif Pada PT Perusahaan Listrik Negara Persero Rayon Ampera - Ranti, Meri; ., Trisinawati (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The purpose of this research is to determine the influence of job resources and job commitment as mediators in proactive behavior. This type of research uses a quantitative research approach. The method of data collection from research on the effect of work resources and work involvement as mediators on proactive behavior is the survey method. The survey was conducted by distributing questionnaires to PT employees. PLN Persero Rayon Ampera. The questionnaire contains questions to measure the studied variables, namely work resources, work commitment and proactive behavior. Data analysis techniques in this research, the researcher analyzed the data by making a questionnaire. So, the management of the data used in this research uses structural equation modeling (SEM) with the method of least partials (PLS) through the computer program or the SmartPLS application. The results of this study explain that job resources have a positive impact commitment to work. The results of the analysis show that professional resources have a positive impact on work engagement. Work engagement has a positive influence on proactive behavior. The results of the analysis also show that work engagement has a positive impact on proactive behavior. Work engagement plays a mediating role in the relationship between job resources and proactive behavior. The results of the analysis show that work engagement plays a mediating role in the relationship between job resources and proactive behavior.